Risk Factors for Uterine Atony in Postpartum Hemorrhage Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Firmansyah Basir; Hurin ‘Afina Gnd; Dwi Handayani; Hartati; Hadrians Kesuma Putra (HM Publisher, 2023)
Background: Uterine atony can be life-threatening for a pregnant woman in labor and bleeding after delivery. It is important to explore the risk factors that can cause uterine atony in order to detect it early and take preventive measures. This study aimed to explore the risk factors for causing uterine atony in postpartum hemorrhage patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study was an analytic observational study with a case-control approach. A total of 52 subjects (13 case group subjects and 39 control group subjects) participated in this study. Risk factor analysis was carried out with the help of SPSS version 25 in univariate and bivariate. Results: Maternal age at delivery is associated with the risk of uterine atony in postpartum hemorrhage patients. Mothers aged less than 20 years or more than 35 years are at risk of experiencing uterine atony by 5.8 times more at risk than mothers aged 20-35 years. The risk factors for parity, prolonged labor, macrosomia, gemelli, hydramnios, induction of labor, history of postpartum hemorrhage, and type of delivery were not associated with uterine atony in postpartum hemorrhage patients, p>0.05. Conclusion: The age of delivery of mothers who are less than 20 years or more than 35 years is a risk factor for uterine atony in postpartum hemorrhage patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.